Sociolinguistics in North Africa - (:unkn) unknown (My University, 2023)
The paper presents a short state of the Arts of Socolinguistic studies in and on North Africa (including Mauritania, Morocco, Algeria, Tunisia, Egypt and North Sudan)
Keywords: African Research